2008
DOI: 10.1007/s12217-008-9099-z
|View full text |Cite
|
Sign up to set email alerts
|

Germination of Arabidopsis Seed in Space and in Simulated Microgravity: Alterations in Root Cell Growth and Proliferation

Abstract: Changes have been reported in the pattern of gene expression in Arabidopsis on exposure to microgravity. Plant cell growth and proliferation are functions that are potentially affected by such changes in gene expression. In the present investigation, the cell proliferation rate, the regulation of cell cycle progression and the rate of ribosome biogenesis (this latter taken to estimate cell growth) have been studied using morphometric markers or parameters evaluated by light and electron microscopy in real micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 25 publications
(24 reference statements)
3
14
0
Order By: Relevance
“…These results are totally consistent with data obtained from spaceflight experiments with A. thaliana, in which the reduction in nucleolar activity was related to alterations in cell proliferation (Matia et al 2005(Matia et al , 2010. Cell proliferation was also enhanced, but with reduced cell growth in A. thaliana root meristematic cells in both real and simulated microgravity (Manzano et al 2009), which the authors consider indicates uncoupling of these two processes, unlike the situation under 1 g. At the same time, a decrease in proliferative activity in root meristematic cells of pea seedlings was found under clinorotation (Artemenko 2005). In A. thaliana, clinorotation affected d1and d3-cyclin gene expression, as shown from in situ hybridisation (Artemenko 2005).…”
Section: Cell Cycle and Nucleolar Activitysupporting
confidence: 90%
See 1 more Smart Citation
“…These results are totally consistent with data obtained from spaceflight experiments with A. thaliana, in which the reduction in nucleolar activity was related to alterations in cell proliferation (Matia et al 2005(Matia et al , 2010. Cell proliferation was also enhanced, but with reduced cell growth in A. thaliana root meristematic cells in both real and simulated microgravity (Manzano et al 2009), which the authors consider indicates uncoupling of these two processes, unlike the situation under 1 g. At the same time, a decrease in proliferative activity in root meristematic cells of pea seedlings was found under clinorotation (Artemenko 2005). In A. thaliana, clinorotation affected d1and d3-cyclin gene expression, as shown from in situ hybridisation (Artemenko 2005).…”
Section: Cell Cycle and Nucleolar Activitysupporting
confidence: 90%
“…Cell proliferation was also enhanced, but with reduced cell growth in A. thaliana root meristematic cells in both real and simulated microgravity (Manzano et al . ), which the authors consider indicates uncoupling of these two processes, unlike the situation under 1 g . At the same time, a decrease in proliferative activity in root meristematic cells of pea seedlings was found under clinorotation (Artemenko ).…”
Section: Cell Cycle and Nucleolar Activitymentioning
confidence: 76%
“…Manzano et al . () showed that cell proliferation and growth are altered in Space due to microgravity. More specifically, cell proliferation appeared enhanced, while cell growth decreased, based on the demonstrated relationship with indicators of nucleolar activity ( e.g .…”
Section: Stress‐induced Responses Common To Various Growth and Reprodmentioning
confidence: 99%
“…Given that there is evidence for perturbations to pollen germination and seedling development due to simulated or Space microgravity, often as a consequence of alterations during the cell cycle, cell wall development, cell enlargement and pollen tube elongation (De Micco et al 2006b,c, 2008Mat ıa et al 2010), these are considered particularly sensitive points in the seed-to-seed cycle in Space. Manzano et al (2009) showed that cell proliferation and growth are altered in Space due to microgravity. More specifically, cell proliferation appeared enhanced, while cell growth decreased, based on the demonstrated relationship with indicators of nucleolar activity (e.g.…”
Section: Stress-induced Responses Common To Various Growth and Reprodmentioning
confidence: 99%
“…Several studies have reported that plant growth is affected by alterations in gravity imposed on plants. For instance, Manzano et al (2009) revealed that cell growth and reproduction differ in microgravity in space. More specifically, cell reproduction increases when growth is reduced, indicating a relationship with nucleolus activity in the microgravity environment ).…”
Section: Discussionmentioning
confidence: 99%